2009
DOI: 10.1103/physrevb.79.115127
|View full text |Cite
|
Sign up to set email alerts
|

Onset of metallic behavior in strained(LaNiO3)n/(SrMnO3

Abstract: ͑LaNiO 3 ͒ n / ͑SrMnO 3 ͒ 2 superlattices were grown using ozone-assisted molecular beam epitaxy. In situ reflection high-energy electron diffraction and x-ray scattering has been used to characterize the structural properties of the superlattices, which are strained to the SrTiO 3 substrates. The superlattices exhibit excellent crystallinity and interfacial roughness of less than 1 unit cell. A metal-insulator transition is observed as n is decreased from 4 to 1. Analysis of the transport data suggests an evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
13
45
0
Order By: Relevance
“…LNO based heterostructures have been grown and transport measurements have revealed a MI transition as the LNO thickness is reduced to only a few unit cells (u.c.) [9,10]. This behaviour is in agreement with the MI transition observed in single ultrathin LNO films [11].…”
supporting
confidence: 78%
“…LNO based heterostructures have been grown and transport measurements have revealed a MI transition as the LNO thickness is reduced to only a few unit cells (u.c.) [9,10]. This behaviour is in agreement with the MI transition observed in single ultrathin LNO films [11].…”
supporting
confidence: 78%
“…studies revealed the composition of the superlattices, average c-axis parameters, and confirmed that they exhibit minimal interfacial mixing and are highly crystalline. 17 Synchrotron diffraction measured along the (00L), shown in Fig. 1(a (1 1 3) peaks confirm the epitaxial layers are coherently strained.…”
mentioning
confidence: 99%
“…17 The sample thicknesses are between 200 and 215Å. Previous structural (00L) in three samples exhibiting distinct satellite peaks due to the coherent superlattice structure (a).…”
mentioning
confidence: 99%
“…'s) [18][19][20]. Several explanations have been proposed in the literature, including Anderson localization, which occurs when the resistance exceeds a critical value (Mott minimum conductivity) below a certain thickness [19,21], and quantum confinement [22,23].…”
mentioning
confidence: 99%